The Quantitative Assessment of the Cyclical Development in Modern Conditions - Dmitriy A. Endovitskiy; Nikolay P. Lyubushin; Nadezhda E.a Babicheva; Tatyana A. Pozhidaeva (Montenegrin Journal of Economics)
The article studies applicability of the resource-oriented approach in assessing the impact of extensive and intensive factors on stable and continuous development of economic systems under cyclic conditions. The quantitative assessment of impact of efficient resource utilization on structural growth rates of the economy dependent on domestic public policy showed that excessive development of financial services makes the economy quite vulnerable to external factors. Results of the research according to the suggested method show that Russian economy has been in crisis since 2006, which matches the downward wave of big economic dynamics cycle described by N. D. Kondratyev